Синтез нечіткого регулятора для керування ВРД без давача положення ротора - Михайлович, Т. І. (Видавництво Львівської політехніки, 2011)
The paper deals with the problem of estimating the magnitude, frequency and also the initial phase of sinusoids from noisy measurement implemented in the discrete time. Within the set-membership identification approach, a new method for deriving lower and upper bounds on these parameters in the presence of an arbitrary bounded noise is advanced.
Keywords: идентификация; множественное оценивание; ограниченная помеха; синусоидальный сигнал; короткая выборка